Robotic posterior retroperitoneal adrenalectomy. Issue 3 (12th June 2015) - Okoh, Alexis Kofi; Yigitbas, Hakan; Berber, Eren; Berber, Eren
<x xml:space="preserve">Abstract</x> Since its initial description by Mercan et al. laparoscopic posterior retroperitoneal (PR) adrenalectomy has served as an alternaltive to the transabdominal (TL) approach for the treatment of adrenal pathologies. Robotic adrenal surgery has been reported to improve surgeon ergonomics and facilitate dissection. In patients with bilateral adrenal masses, PR adrenalectomy may be the approach of choice. We herein describe the technique, discuss its limitations and present a critical review of the current literature. J. Surg. Oncol. 2015; 112:302–304. © 2015 Wiley Periodicals, Inc.